Implementing The Crc In Child Protection Policies In The Case Of Barnahus And Refugee Children In Sweden Within A Human Security Framework - Alifia, Ahliza (Jayapangus Press, 2025)
Violence and abuse against children, including refugee children, remain a serious challenge in Sweden despite the existence of a strong legal framework. Refugee children often face double trauma, legal uncertainty, and limited access to basic services that threaten their right to life and development. This study aims to analyze the implementation of the Convention on the Rights of the Child (CRC) through the application of the Barnahus model within the framework of human security to strengthen the protection of refugee children in Sweden. Using qualitative methods through literature review, policy analysis, and jurisprudence, this study evaluates the effectiveness of Barnahus as a multidisciplinary approach that integrates social, health, and legal services. The analysis results indicate that Barnahus is able to provide a safe space for children who are victims of violence, minimize the risk of repeated trauma through cross-sector coordination, and ensure children's right to be heard in accordance with CRC principles. However, its implementation for refugee children still faces challenges, such as cultural adaptation limitations, lack of specialized psychosocial support for refugees, and legal uncertainty that affects children's sense of safety. This study concludes that Barnahus optimization must be carried out by adding culturally sensitive training, using professional interpreters, and integrating with education, housing, and mental health services so that the protection of refugee children is holistic. This approach aligns with the concept of human security, which emphasizes the protection of children's rights, well-being, and dignity as top priorities, ensuring that child protection policies are not only reactive but also proactive and sustainable.